Hermenêutica no direito tributário: o caso Sebrae - Musse, Virgílio Alves (2024)
This paper aims to investigate the role of legal hermeneutics in the interpretation and application of tax rules, focusing on the judgment in Extraordinary Appeal No. 603.624. This decision discussed the constitutionality of the contribution collected in favor of the Brazilian Micro and Small Business Support Service (Sebrae), the Brazilian Trade and Investment Promotion Agency (Apex-Brasil) and the Brazilian Industrial Development Agency (ABDI), and was selected for case analysis. The study analyzes how hermeneutic principles and guidelines are applied in the specific context of tax law, considering the complexity of relations between the state and taxpayers today. Through an interdisciplinary approach, hermeneutic theories and fundamental concepts of Tax Law are explored, with the aim of understanding the phenomenology of the incidence of the legal norms related to the case analyzed. The research also investigates the importance of proper legal exegesis for the liberal democratic rationality of the tax system, highlighting the conflicts and challenges in the act of interpreting and applying the law in the context of the Sebrae case and, by extension, in the broader context of Brazilian tax law